2019
DOI: 10.1177/1350650119873232
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation erosion resistance of ZrC nanoceramic coating

Abstract: A ZrC nanoceramic coating was prepared on the bare 316 stainless steel for improving the cavitation erosion resistance by the double glow discharge sputter technique. The phase constitution and surface microstructure of the ZrC nanoceramic coating were characterized by X-ray diffraction, scanning electron microscope, and transmission electron microscopy. A 10-µm-thick ZrC nanoceramic coating exhibited equiaxed grains with an average grain size of 9 nm. The adhesion strength and mechanical properties for the Zr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A moderate wear regime was observed when H a K IC_abrasive /H m ratio (K IC_abrasive is the fracture toughness of the erodent material) is less than 2, while a moderate-severe transition regime was observed when the ratio is between 2 and 4. A 10 μm-thick ZrC ceramic coating with grain size of 6 nm was prepared on bare 316 stainless steel using double glow discharge sputter technique, and its cavitation erosion resistance was characterized by the combination of an ultrasonic vibration system with an electrochemical workstation [211]. The results showed that the volume loss of the ZrC nanoceramic coating was only 46% of the 316 stainless steel after cavitation test, and erosion damage of the ZrC nanoceramic coating was significantly decreased as compared to the uncoated 316 stainless steel.…”
Section: Wear Behavior and Mechanismsmentioning
confidence: 99%
“…A moderate wear regime was observed when H a K IC_abrasive /H m ratio (K IC_abrasive is the fracture toughness of the erodent material) is less than 2, while a moderate-severe transition regime was observed when the ratio is between 2 and 4. A 10 μm-thick ZrC ceramic coating with grain size of 6 nm was prepared on bare 316 stainless steel using double glow discharge sputter technique, and its cavitation erosion resistance was characterized by the combination of an ultrasonic vibration system with an electrochemical workstation [211]. The results showed that the volume loss of the ZrC nanoceramic coating was only 46% of the 316 stainless steel after cavitation test, and erosion damage of the ZrC nanoceramic coating was significantly decreased as compared to the uncoated 316 stainless steel.…”
Section: Wear Behavior and Mechanismsmentioning
confidence: 99%
“…The mass loss of the untreated and LSMed samples in deionised water is 35 ± 1 and 14 ± 0.3 mg, whereas the mass loss in 3.5 wt% NaCl solution is 40 ± 0.6 and 20 ± 0.3 mg after 8-h CE, respectively. The mean depth of erosion ( MDE ) and the mean depth of erosion rate ( MDER ) can be used to evaluate CE resistance and calculated as follows: 357 where Δw is the mass loss (mg), ρ is the density of the materials (g/cm 3 ), s is the eroded area (1 cm 2 in this study), Δ T is the interval time (h), MDE in μm and MDER in μm/h. The CE resistance R e (h μm −1 ) is the reciprocal of MDER.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the CE resistance of the coating was better than that of the 304L stainless steel substrate, and higher bias voltage would make the coating hard, but it had little effect on elastic recovery, which improved the CE resistance of the coating to the greatest extent. Ding et al 20 fabricated ZrC nanoceramic coating on the surface of 316 stainless steel. It was found that the hardness of the coating was four times that of the 316 stainless steel and the cavitation loss was only 46% that of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The Cr/CrSiN-10 multilayer coating also exhibited lower erosion wear rate (0.05 μm•s -1 ) compared with Cr/CrSiN-1 coating (0.15 μm•s -1 ). Hard coatings of ZrC [518], ZrN [519], and Ta 1-x W x C y [520] films were respectively deposited by sputtering. The ZrC nanoceramic coating showed higher corrosion resistance than the 316 stainless steel under cavitation erosion condition.…”
Section: Vacuum Depositionsmentioning
confidence: 99%